Implementation of KKNI-Based Curriculum Management in the English Education Study Program to Improve the Quality of Graduates at Muhammadiyah University Tangerang - Mariyanah , Siti (The International Journal of Education Management and Sociology, 2024)
The purpose of this research is to investigate: (1) the planning, implementation, and evaluation of the curriculum based on the Indonesian National Qualifications Framework (KKNI) in the English Education Study Program, and (2) the supporting and inhibiting factors. This research uses a qualitative approach to describe the phenomena observed in the field. Data were collected through interviews guided by predetermined frameworks and instruments, observations, and document studies related to the curriculum of the English Education Study Program. The findings reveal that the curriculum planning aligns with the vision and mission of the English Education Study Program, which is geared towards enhancing the quality of graduates and professionalism through learning processes that meet the expected learning outcomes. The implementation of the curriculum, as designed under the KKNI framework, is reinforced by a well-structured management plan for the English Education Program. Evaluation of the curriculum's implementation is shown to enhance graduate quality, as the study program's graduates consistently demonstrate improvements in quality. The research outcomes include: (1) solving issues related to English language teaching, (2) providing conclusions on these challenges, (3) planning, implementing, managing, evaluating, and improving English language teaching, (4) taking responsibility for the quality of the outcomes, and (5) producing graduates equipped with the skills needed to compete in the job market